Time-Space Clustering of Human Brucellosis, California, 1973–1992 - Geoffrey T. Fosgate; Tim E. Carpenter; Bruno B. Chomel; James T. Case; Emilio E. DeBess; Kevin F. Reilly (Emerging Infectious Diseases, 2002)
Infection with Brucella spp. continues to pose a human health risk in California despite great strides in eradicating the disease from domestic animals. Clustering of human cases in time and space has important public health implications for understanding risk factors and sources of infection. Temporal-spatial clustering of human brucellosis in California for the 20-year period 1973–1992 was evaluated by the Ederer-Myers-Mantel, Moran’s I, and population-adjusted Moran’s I procedures. Cases were clustered in concentrated agricultural regions in the first 5-year interval (1973–1977). Time-space clustering of human brucellosis cases in California late in the 20-year study period may reflect the distribution of Hispanic populations. Public health programs in California should focus on educating Hispanic populations about the risk of consuming dairy products, such as soft cheeses, made from unpasteurized milk.